Are Leadership Fairness, Psychological Distress, and Role Stressors Interrelated? A Two-Wave Prospective Study of Forward and Reverse Relationships - Nielsen, Morten B.; Christensen, Jan O.; Finne, Live B.; Knardahl, Stein (Frontiers in Psychology, 2018)
While previous research has mainly considered leadership as an antecedent to psychological distress and role stressors (i.e., role ambiguity and role conflict) among subordinates, a reverse relationship where these variables influence reports of leadership is also possible. To determine the directionality of the associations this two-wave prospective study assesses bidirectional relationships between fair leadership and role stressors and examines whether psychological distress mediates the reciprocal associations between fair leadership and the role stressors. Analyses were conducted in a sample of 6,790 Norwegian employees with a two-year time-lag between measurement points. Fair leadership was associated with lower stability adjusted role ambiguity, but not role conflict, over time. Role conflict, but not role ambiguity, was related to subsequent reports of the immediate leader as less fair. Psychological distress did neither mediate the relationship between fair leadership and subsequent reports of role stressors, nor the association between role stressors and subsequent reports of fair leadership. The findings suggest that the fair leadership – role stressor association is not a one-directional process, but that exposure to role stressors also influence subordinates’ perceptions of leadership. An implication of the findings is that theoretical models of organizational leadership should include this reverse impact of role stressors. To reduce the effects of role stressors, organizations could set consistent, clear and attractive goals and provide employees with necessary information for conducting their work tasks in order to help workers understand and master their roles at the workplace.